Estimation of Body Fluid Volume by Bioimpedance Spectroscopy in Patients with Hyponatremia - Kim, Jae Seok (Yonsei University College of Medicine, 2014)
PURPOSE: Estimation of body fluid volume in hyponatremia is useful for diagnosis and therapeutic decision-making. Physical examination has been generally used to estimate body fluid volume, but it depends on the physician's abilities. Bioimpedance spectroscopy has been suggested to be a reliable method for the estimation of body fluid volume. Therefore, this study investigated whether bioimpedance spectroscopy could replace physical examination in hyponatremia. MATERIALS AND METHODS: The study included 30 patients with hyponatremia. At the time of the initial visit, body fluid volume was estimated simultaneously by both physical examination and bioimpedance spectroscopy. Estimation of body fluid status by clinical diagnosis was performed as well, which determined body fluid status corresponds with the most likely cause of hyponatremia (clinical body fluid estimation). RESULTS: The results of body fluid volume estimated by physical examination, bioimpedance spectroscopy, and clinical body fluid estimation showed that 9, 10, and 9 patients, respectively, were hypervolemic; 13, 15 and 16 patients, respectively, were euvolemic; and 8, 5, and 5 patients, respectively, were hypovolemic. Cohen's kappa analysis showed a significant agreement between physical examination and bioimpedance spectroscopy (kappa coefficient, 0.632, p<0.001). In addition, bioimpedance spectroscopy showed a higher level of agreement with clinical body fluid estimation than physical examination (kappa coefficient, 0.602 vs. 0.524). CONCLUSION: This study suggests that bioimpedance spectroscopy could replace physical examination for estimating body fluid status in hyponatremia. In addition, bioimpedance spectroscopy might correspond better with clinical diagnosis than physical examination in the estimation of body fluid status in hyponatremia.